2014
DOI: 10.1007/s10584-014-1127-y
|View full text |Cite
|
Sign up to set email alerts
|

Thinking globally and siting locally – renewable energy and biodiversity in a rapidly warming world

Abstract: Increasing greenhouse gas emissions are projected to raise global average surface temperatures by 3˚-4°C within this century, dramatically increasing the extinction risk for terrestrial and freshwater species and severely disrupting ecosystems across the globe. Limiting the magnitude of warming and its devastating impacts on biodiversity will require deep emissions reductions that include the rapid, large-scale deployment of low-carbon renewable energy. Concerns about potential adverse impacts to species and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 13 publications
0
34
0
Order By: Relevance
“…Siting USSE installations in places already impacted by humans (e.g., parking lots, rooftops) reduces the likelihood that adverse environmental impacts will occur and can exceed generation demands for renewable energy goals in places with moderate-to high-quality solar resources (8,10,13), including California. When sites within the built environment are inaccessible, siting that minimizes land use and land cover change within areas acting as carbon sinks, avoids extirpation of biodiversity, and does not obstruct the flow of ecosystem services to residents, firms, and communities, can serve to mitigate adverse environmental impacts (2,3,9,10,14,15). Siting within the built environment also reduces the need for complex decision making dictating the use of land for food or energy (16).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Siting USSE installations in places already impacted by humans (e.g., parking lots, rooftops) reduces the likelihood that adverse environmental impacts will occur and can exceed generation demands for renewable energy goals in places with moderate-to high-quality solar resources (8,10,13), including California. When sites within the built environment are inaccessible, siting that minimizes land use and land cover change within areas acting as carbon sinks, avoids extirpation of biodiversity, and does not obstruct the flow of ecosystem services to residents, firms, and communities, can serve to mitigate adverse environmental impacts (2,3,9,10,14,15). Siting within the built environment also reduces the need for complex decision making dictating the use of land for food or energy (16).…”
Section: Significancementioning
confidence: 99%
“…Solar energy systems are highly modular ranging from small-scale deployments (≤1 MW; e.g., residential rooftop modules, portable battlefield systems, solar water heaters) to centralized, utility-scale solar energy (USSE) installations (≥1 MW) where a large economy of scale can meet greater energy demands. Nonetheless, the diffuse nature of solar energy necessitates that large swaths of space or land be used to collect and concentrate solar energy into forms usable for human consumption, increasing concern over potential adverse impacts on natural ecosystems, their services, and biodiversity therein (2)(3)(4)(5).…”
mentioning
confidence: 99%
“…
Allison et al (2014) is a provocative piece that highlights (1) the risks for ecosystems as the climate changes and (2) the tradeoffs that must be considered (i.e., the specific risks for one particular ecosystem against another) in the broader context of the global implications of (3) climate change and policy responses. In their abstract, they state that (selectively quoted with my emphasis in italics):

Increasing greenhouse gas emissions are projected to raise global average surface temperatures by 3°-4°C within this century, dramatically increasing the extinction risk for terrestrial and freshwater species and severely disrupting ecosystems across the globe.

…”
mentioning
confidence: 99%
“…The risk-based framing adopted by Allison et al (2014) was born in the Summary for Policymakers of the Synthesis Report of the Fourth Assessment Report of the Intergovernmental Panel on Climate Change (IPCC 2007). In its final section, and in words that were authored by Steven Schneider and unanimously approved by all of the countries involved in the United Nations Framework Convention on Climate Change, the IPCC concluded that:…”
mentioning
confidence: 99%
See 1 more Smart Citation